Drivers of productivity in Vietnamese SMEs: The role of management standards and innovation - Elisa Calza; Micheline Goedhuys; Neda Trifković (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Using a rich panel dataset of SMEs active in the manufacturing sector in Viet Nam, this paper investigates the drivers of firm productivity, focusing on the role played by international management standards certification. We develop and test the hypothesis that, controlling for technological innovation (product and process) and other variables related to technological capabilities, international standards are still conducive to higher productivity, through improved management practices associated with their adoption. In line with the requirement of continuous improvement implied by most international standards, the main findings show that the possession of an internationally recognized standard certificate leads to significant productivity premium. We further investigate the relationship between technological innovation and standard adoption. We find that the likelihood of certificate adoption is higher when firms implement technological innovations and that the effect of certification on productivity is particularly strong for firms with technological innovation.
Keywords: D22; D24; L20; O12; O30; 330; management standards; ISO certification; technological innovation; productivity; Viet Nam